2003
DOI: 10.4269/ajtmh.2003.68.128
|View full text |Cite
|
Sign up to set email alerts
|

Community Reactions to the Introduction of Permethrin-Treated Bed Nets for Malaria Control During a Randomized Controlled Trial in Western Kenya

Abstract: Prior to implementation of a randomized controlled trial of insecticide (permethrin)-treated bed nets (ITNs) in western Kenya, ethnographic studies were conducted to understand local perceptions of disease, sleeping patterns, and other factors that might affect use of ITNs. Educational activities took place prior to distribution, but immediately after distribution in Asembo only approximately half of the ITNs were in use. A qualitative study was then conducted to identify the community's perceptions about ITNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 20 publications
5
60
1
Order By: Relevance
“…People who did not use ITNs cited discomfort due to heat and humidity and the high cost of ITNs as reasons for non-use (Nuwaha 2002;Mbonye et al 2006a). In Kenya, although malaria was perceived to be an important disease, ITNs were believed to be partially beneficial because of the perception that malaria has multiple causes and the belief that chemicals used to treat ITNs were associated with family planning (Alaii et al 2003). However, 36% of Malawian women did not know what causes malaria and 95% of them mentioned one or more symptoms of malaria (Launiala and Kulmala 2006).…”
Section: Discussionmentioning
confidence: 93%
“…People who did not use ITNs cited discomfort due to heat and humidity and the high cost of ITNs as reasons for non-use (Nuwaha 2002;Mbonye et al 2006a). In Kenya, although malaria was perceived to be an important disease, ITNs were believed to be partially beneficial because of the perception that malaria has multiple causes and the belief that chemicals used to treat ITNs were associated with family planning (Alaii et al 2003). However, 36% of Malawian women did not know what causes malaria and 95% of them mentioned one or more symptoms of malaria (Launiala and Kulmala 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Elsewhere, the cold rainy season has been reported to be a key reason for using MBNs [31, 32]. Some of the challenges of the study include the fact that there was no established list of households in any of the health areas and so systematic simple random selection of households was a little difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Novel reports about knowledge, attitudes, and practices relating to malaria and its control are not lacking but these reports concluded that misconceptions on malaria transmission and risk factors still exist with negative impact on malaria control programmes [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%